Use of Iodine Contrast Volume and Low Radiation Dose Abdominal CT-Scan Examination New Standard Procedure Patient Safety Radiology Services - Purwanto Purwanto; Akhirida Putri (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Radiodiagnostic and interventional radiology services (RIR) is one of the services that has a high risk to patient safety, one of the risks that exist in RIR services is the use of iodine-based contrast materials with a large volume that can increase the occurrence of CIN (Contrast Induced Nepropathy), CT scan of the abdomen with contrast also has a potential risk of radiation exposure received by the patient. Efforts need to be made to improve new protocol standards that prioritize patient safety. The research method was carried out by an experimental method followed by the implementation of the new standard protocol CT Abdominal Scan using contrast by involving 10 samples, both CT Scan Abdominal Examination in contrast to the old standard and with the new standard. The results of experimental research using phantom materials show that the use of low volume contrast and low radiation dose produces a higher enhancement or opacity (HU) value when compared to using low contrast volume and high radiation dose. The results of the protocol implementation of 10 samples evaluated by 2 observers showed that there was no difference in the value of anatomical images between the old and new protocols. Anova's one-way analysis showed that the value of F-value = 0.22 and p-value = 0.88 because the p-value was greater than 0.05, there was no significant difference between the two CT Scan protocols. The results of experiments with phantom and the implementation of new standards using contrast volume and low radiation dose have proven to be an alternative to the new protocol standard CT Abdominal Contrast Scan based on patient safety.